Development of Interactive Powerpoint Media Based on Ethnomathematics of Batik Kawung Motif on Flat Building Material in Elementary School - Anisa Fitri Rahmawati; Achmad Fatoni (Universitas Negeri Makassar, 2023)
The research aims to produce an interactive powerpoint learning media based on ethnomathematics of batik kawung motifs on flat building material in elementary schools that is valid and practical. This type of research is development research (Research and Development) with the ADDIE research model. The subjects in this study were media experts, material experts and grade III students from two different schools. Third grade students of SD Negeri Jeruk 2 amounted to 8 people who were categorized as small groups and SD Negeri Girimargo 1 amounted to 22 people who were categorized as large groups. Data analysis used two methods, namely descriptive qualitative and descriptive quantitative. The results of the assessment by the media expert test were 80%, the material expert test by two testers and both obtained results of 76.6%, the expert test assessment was qualified as good. The small group trial amounted to 95.31% and the large group test amounted to 91.9%, the assessment of students was qualified as very good. The pre-test results in the small group obtained an average of 37.5 while the large group was 28.5, both of which were in low qualifications. While the post-test results in the small group obtained an average of 90 with high qualifications, and the large group obtained an average of 75.2 with moderate qualifications. Therefore, this learning media development research is feasible and can improve students' math learning outcomes.